EFEKTIVITAS PROGRAM PEMUTIHAN PAJAK KENDARAAN BERMOTOR DI PROVINSI SUMATERA SELATAN TAHUN 2021 - Austin, Trecy; Alriadho, Ahmad; Tholib, Ibrahim; Febrianza, Muhammad (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2023)
The purpose of this study was to determine the extent to which the effectiveness of the Motor Vehicle Tax Bleaching Program in Increasing Local Revenue for the Province of South Sumatra in 2021. The theory used in this research is the theory of effectiveness by Richard M. Steers. The research method used is a qualitative method. There were 8 people who were used as informants in this study. The results of this study used an analysis of the research focus on the achievement of objectives, integration, adaptation which showed that based on the research focus the objectives were good and the design objectives had been successful and achieved. Furthermore, judging from the research focus, the integration of program socialization is going well because it utilizes digitalization as a means of socialization. and finally the focus of research Adaptation adjustments to the program are carried out well because of the coordination of the traffic police to carry out a network of motor vehicle raids that are still not compliant with motor vehicle taxes.